The export-diversifying impact of and U.S. foreign direct investments in indian manufacturing sector - Rashmi Banga (Indian Council for Research on International Economic Relations (ICRIER), 2003)
The paper highlights the export-diversifying impact of FDI in a developing country. FDI from a particular source may lead to export diversification of developing countries if it positively affects the export-intensity of the non-traditional export sector. Indirectly, FDI may encourage export diversification by spillover effects on the exportintensity of domestic firms in the non-traditional export sector. The empirical results forthe Indian economy in the post liberalization period show that FDI from U.S. has led to diversification of India's exports both directly as well as indirectly. However, Japanese FDI has had no significant impact on India's exports
Keywords: F14; F23; L6; O1; 330; FDI and Exports; Indian Exports; Export-Diversification; Japanese FDI; U.S. FDI